Are you what you eat? Assessing intracellular effects of supplemental lipid within mouse (C2C12) skeletal muscle cells - Montano, Dominique, author; Kanatous, Shane, advisor; Bell, Christopher, advisor; Engle, Terry, committee member; Florant, Gregory, committee member (Colorado State University. Libraries, 2021)
The expression of myoglobin, an oxygen-binding protein, facilitates aerobically-powered dives by effectively distributing a finite oxygen supply during breath-hold dives in marine mammals (Costa 2004, Kanatous et al. 1999, Wright 2006). Multiple factors have been experimentally shown to contribute to increasing myoglobin expression, thus influencing aerobic capacity. Among the known expression pathways, the most recent and least studied involves a link between lipid supplementation and increased myoglobin expression. We are unaware of the specific conditions that drive this expression, and whether or not fatty acids play an intracellular role in upregulating myoglobin. This work elucidates the effects of lipid supplementation on the expression of myoglobin in terrestrial mammals, as well as enhances our understanding of cues that initiate the expression of factors contributing to the positive development of aerobically-based exercise in the whole animal. In order to understand these lipid influences on an aerobically-adapted animal such as a marine mammal, we focused on developing experimental designs and applications geared towards a model mammalian system of C2C12 mouse cells. Lipids possess the capacity to influence aerobic ability in mammalian models, whether through marine mammals' reliance on lipid metabolism to power aerobically-based exercise, regulating mitochondrial respiration, fatty acid metabolism that generates increased ATP from oxidative phosphorylation relative to metabolic pathways like glycolysis, lipids acting as ligands to affect genes that contribute to aerobic capacity, or lipid supplementation that increases myoglobin expression. Multiple studies from our lab have shown that lipid present in the media upregulates myoglobin in C2C12 cells, driving expression of the protein in conjunction with other elements. Although we have determined a link between lipid supplementation and myoglobin expression, the particular intracellular effects ranging from uptake, transporter protein regulation, and either storage, metabolism, or specific effects directly affecting myoglobin expression still remain to be uncovered. The factors and conditions that regulate myoglobin expression are extensive, and lipids as an avenue to myoglobin expression is a relatively new exploration that will have applications for numerous areas of physiological research. This work has applications in multiple mammalian models, including humans, and will serve to enhance our understanding of the factors that drive aerobically-based endurance exercise, as well as understanding the cues and stimuli required to increase expression of key factors that regulate aerobic capacity in mammalian systems.
Keywords: cell culture; mouse; seals; marine mammals; c2c12; myoglobin